Cambridge reading: what for?(big book) - Gillham, Bill; Ayliffe, Alex (Cambridge University Press UK, 1998)
This is a "Big Book" version of the popular Beginning to Read phase title "What For?". Cambridge Reading is a new reading scheme which provides stimulating books and support materials for the teaching of reading and the development of literacy throughout the primary years